Immune Dysregulation and Trophoblastic Dysfunction as a Potential Cause of Idiopathic Recurrent Pregnancy Loss - Sara Vasconcelos; Ana Costa Braga; Ioannis Moustakas; Bruno Cavadas; Mariana Santos; Carla Caniçais; Carla Ramalho; Susana M. Chuva de Sousa Lopes; Cristina Joana Marques; Sofia Dória (Biology)
Recurrent pregnancy loss (RPL) is a multifactorial condition affecting 1–5% of couples, often with unclear etiology. Idiopathic pregnancy losses (iPLs) are particularly challenging due to unknown molecular mechanisms. This study investigates the transcriptomic profiles of first-trimester products of conception (POC) from iPLs to uncover underlying molecular pathways. We performed RNA-sequencing on nine POC samples, identifying two distinct clusters enriched in trophoblast and decidual cells. Deconvolution analysis revealed reduced syncytiotrophoblast (STB) cells, with increased cytotrophoblast (CTB) and extravillous trophoblast (EVT) cells in iPLs. Gene Set Enrichment Analysis highlighted immune pathways enrichment in both villous trophoblasts and decidua. Gene ontology (GO) analysis of downregulated genes implicated hormonal and endocrine processes, consistent with STB reduction, while upregulated genes were associated with MHC protein complex and immune system processes, aligning with EVT increases. Histological analysis showed chronic histiocytic intervillositis (CHI) in iPL samples, supporting maternal immune dysregulation in unexplained RPL. Together, transcriptomic and histological analyses indicate that immune signaling dysregulation and impaired trophoblast differentiation may underlie unexplained iPLs. These findings bridge molecular and histopathological evidence, underscoring the interplay between trophoblast dysfunction and immune imbalance. Our results provide insights into iPL pathogenesis, highlighting potential biomarkers that may contribute to improved diagnosis and future research.